Organizational Pride Mediating Strategic Thinking and Sustainable Innovation: A Study on the Saudi Postal Corporation - D. Alshrari, Abdullah; M. Al-Ajlouni, Mahmoud; Ali Saad, Mohamed (European Journal of Sustainable Development, 2025)
Through its application to the Saudi Postal Corporation in Jeddah, Saudi Arabia, this study aimed to determine the mediating role of organizational pride in connecting strategic thinking and innovative behavior. The researcher used a descriptive analytical approach in this study, gathering theoretical data from library sources, in addition to designing a questionnaire consisting of (37) phrases that were distributed to (311) individuals working in the Saudi Postal Corporation in Jeddah, the study’s hypotheses were tested and data was analyzed using the statistical software for social sciences (SPSS). The path analysis method was relied upon to verify the presence of indirect effects of strategic thinking on innovative behavior by focusing organizational pride, and the study discovered a remarkable effect of strategic thinking on organizational pride, along with the significant impact of strategic thinking on innovative behavior. The results also showed that organizational pride partially mediates the relationship between strategic thinking and innovative behavior, these findings may help to focus more on organizational pride in strengthening the relationship between strategic thinking and innovative behavior. Keywords: Strategic thinking, Organizational pride, Innovative behavior, Saudi Postal Corporation